Incidence of Leptospirosis infection in the East Zone of Sao Paulo City, Brazil - Miyazato, Kátia Eiko; Fonseca, Alexandre L.A.; Caputto, Luciana Z.; Rocha, Katya C.; Azzalis, Ligia A.; Junqueira, Virginia B.C.; Pereira, Edimar C.; Chaves, Loide C.; Feder, David; Corazzini, Roseli; Abreu, Luiz Carlos de [UNESP]; Valenti, Vitor Engrácia [UNESP]; et al. (Springer Nature, 2013)
Background: Leptospirosis is a zoonosis which is spread through contamined running water. This contaminations is seriously affected by the flooding which occurs in the area surrounding the Aricanduva river. The transmission of the disease results mainly from the contact of water with soil contaminated by the urine of infected animals. We aimed to conduct an epidemiological survey on Leptospirosis cases in Sao Paulo East Zone area. Method. The analysis conducted in this study was based on data collected from the health authorities of that region close the Aricanduva river between 2007 and 2008 years, which give the rates of confirmed cases, mortality and death from human Leptospirosis. Other information concerned with the relationships among rainfall index, points of flooding and incidence of Leptospirosis. Results: We observed a direct and important water contamination. Records of flooding points and dates of the reported cases in the region showed a direct relationship from which the period of higher rainfall also recorded an increase in cases. The annual record of the city and the region and rainfall regions also presented correlation. Conclusion: The association between the indices of flooding and Leptospirosis cases indicates that preventive measures are necessary to avoid exposing the community. © 2013 Miyazato et al.; licensee BioMed Central Ltd.
Keywords: Epidemiological survey; Laboratory methods; Points of flooding; Precipitation index; rain; Brazil; flooding; health survey; human; incidence; leptospirosis; major clinical study; mortality; water contamination